Tilapia (Oreochromis niloticus) as a Putative Reservoir Host for Survival and Transmission of Vibrio cholerae O1 Biotype El Tor in the Aquatic Environment - Hounmanou, Yaovi Mahuton Gildas; Mdegela, Robinson H.; Dougnon, Tamegnon Victorien; Madsen, Henry; Withey, Jeffrey H.; Olsen, John E.; Dalsgaard, Anders (Frontiers in Microbiology, 2019)
Studies have reported the occurrence of V. cholerae in fish but little is known about the interaction between fish and toxigenic V. cholerae as opposed to phytoplankton, which are well-established aquatic reservoirs for V. cholerae. The present study determined the role of tilapia (Oreochromis niloticus) as a reservoir host for survival and transmission of V. cholerae in aquatic environments. Three experiments were performed with one repetition each, where O. niloticus (~2 g) kept in beakers were inoculated with four V. cholerae strains (5x107 cfu/mL). Firstly, infected tilapia were kept in stagnant water and fed live brine shrimp (Artemia salina) larvae daily. Secondly, infected tilapia were kept without feeding and water was changed every 24 h. Thirdly, infected tilapia were fed and water was renewed daily. Infected tilapia and non-infected controls were sacrificed on days 1, 2, 3, 7 and 14 post-inoculation and V. cholerae were enumerated in intestinal content and water. Another experiment assessed the transmission of V. cholerae from infected to non-infected tilapia. The study revealed that El Tor biotype V. cholerae O1 and V. cholerae non-O1 colonized tilapia intestines and persisted at stable concentrations during the second week of the experiment whereas the Classical biotype was undetectable after one week. In stagnant water with feeding, V. cholerae counts dropped to 105 cfu/ml in water and from 107 to 104 cfu/intestine in fish after 14 days. When water was renewed, counts in water decreased from 107 to 103 cfu/ml and intestinal counts went from 106 to 102 cfu/intestine regardless of feeding. All strains were transmitted from infected to naïve fish after 24 h of cohabitation. Tilapia like other fish may play an essential role in the survival and dissemination of V. cholerae O1 in aquatic environments, e.g. the seventh pandemic strains mostly. In this study, tilapia were exposed to high concentrations of V. cholerae to ensure initial uptake and follow-up studies with lower doses resembling natural concentrations of V. cholerae in the aquatic environment are needed to confirm our findings.